2011
DOI: 10.1210/en.2011-0255
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Stimulates Activin βA mRNA Expression in Human Skin Fibroblasts Through the MAPK Pathways, the Nuclear Factor-κB Pathway, and Prostaglandin E2

Abstract: During mouse skin wound healing, mRNAs encoding IL-1, activins, and TGF-βs significantly increased. To elucidate involvement of IL-1 in the regulation of activins and related factors in the wounded skin, human foreskin fibroblasts were stimulated with IL-1β, and levels of mRNAs encoding activins, TGF-βs, and follistatin family proteins were examined by quantitative real-time PCR. IL-1β increased activin βA (INHBA) and follistatin (FST) mRNA expression within 6 h. A p38 MAPK inhibitor, SB202190, a MAPK/ERK kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 52 publications
(84 reference statements)
3
23
1
Order By: Relevance
“…Skin equivalents were prepared as reported previously [21]. Newborn human foreskin keratinocytes and fibroblasts were purchased from KURABO.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Skin equivalents were prepared as reported previously [21]. Newborn human foreskin keratinocytes and fibroblasts were purchased from KURABO.…”
Section: Methodsmentioning
confidence: 99%
“…Messenger RNA levels were measured by quantitative realtime PCR as described previously [21]. Upper and lower primers were selected from different exons to avoid amplification of genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐1 is a main inflammatory factor during wound healing or other inflammatory events in the skin. Human interleukin‐1 alpha gene ( IL1A ) is highly expressed in the epidermal keratinocytes, and expression of both Il1a and Il1b mRNAs noticeably increase after wounding in the mouse skin . Prostaglandin E 2 (PGE 2 ) is also a key mediator of inflammatory events in the skin.…”
mentioning
confidence: 99%
“…IL‐1 is well known to stimulate expression of PTGS2 gene in a variety of cells . Ptgs2 mRNA expression in the mouse skin also increase during wound healing, and wound exudate contains high concentrations of PGE 2 . A previous study showed that, in co‐culture of dermal fibroblasts with epidermal keratinocytes, keratinocyte‐derived IL‐1α induced an increase in PGE 2 production and PTGS2 activity in fibroblasts .…”
mentioning
confidence: 99%